ASSESSMENT AND FORECASTING OF THE FINANCIAL CONDITION OF THE COMPANY BY THE METHOD OF DISCRIMINANT FUNCTIONS - Savchuk, L. M.; Vozianova, V. I.; Kovalchuk, H. K. (Science and Transport Progress, 2007)
The original model of estimation of the financial state of enterprise on two integral financial criteria is grounded in work – indexes of profitability and liquidity of assets. It is taken this approach for prognostication of the financial state of enterprise and development of recommendations for stabilization of the folded situation.